Cyber risk and the U.S. financial system: A pre-mortem analysis - Thomas M. Eisenbach; Anna Kovner; Michael Junho Lee (Federal Reserve Bank of New York, 2021)
We model how a cyber attack may be amplified through the U.S. financial system, focusing on the wholesale payments network. We estimate that the impairment of any of the five most active U.S. banks will result in significant spillovers to other banks, with 38 percent of the network affected on average. The impact varies and can be larger on particular days and in geographies with concentrated banking markets. When banks respond to uncertainty by liquidity hoarding, the potential impact in forgone payment activity is dramatic, reaching more than 2.5 times daily GDP. In a reverse stress test, interruptions originating from banks with less than 10 billion in assets are sufficient to impair a significant amount of the system. Additional risk emerges from third-party providers, which connect otherwise unrelated banks.
Keywords: G12; G21; G28; 330; cyber; banks; networks; payments